Idiopathic Sudden Sensorineural Hearing Loss in Different Ages: Prognosis of Patients With Initial Total Hearing Loss - Xiong, Wenping; Dai, Qinglei; Wang, Yingjun; Hou, Zhiqiang; Lu, Kunpeng; Sun, Xiao; Duan, Fujia; Wang, Haibo; Zhang, Daogong; Wang, Mingming (Frontiers in Psychology, 2022)
Objective: This study aimed to analyze the hearing improvement and prognosis factors of idiopathic sudden sensorineural hearing loss (ISSNHL) in different ages with initial total hearing loss Methods: We reviewed the medical records of 5,711 hospitalized patients with ISSNHL from 2016 to 2021 in our center. All of the patients had been treated with uniform combination medicines therapy. After excluding the patients with initial not total hearing loss and diagnosed with clear etiology, 188 patients were enrolled in this study and divided into six age groups (18–30 y, 31–40 y, 41–50 y, 51–60 y, 61–70 y, ≥71 y). In all groups, increases in pure tone average (PTA) 1-month after treatment, effective rate, and clinical characteristics (vertigo, tinnitus, hospital stay, comorbidity, and inner ear MRI) were analyzed. Results. Among the 188 enrolled patients, 86% of the patients had vertigo and 2% of the patients had the mean hearing threshold smaller than 50dB; complete recovery was seen in 0.5% of patients and marked recovery was seen in 43% of patients. The mean 1-month post-treatment PTAs were: 18–30 y: 80±7.5 dB; 31–40 y: 100±9.0 dB; 41–50 y: 99±8.3 dB; 51–60 y: 101±8.6 dB; 61–70 y: 96±9.6 dB; ≥71 y: 88±13.0 dB. Compared with the other groups, the 18–30 y group showed better recovery of hearing threshold in five frequencies (0.25 kHz, 0.5 kHz, 1 kHz, 2 kHz, and 4 kHz, respectively at octave or semi-octave frequencies under air conduction), and the recovery of hearing threshold at 0.25 Hz and 0.5 Hz was better than the recovery at 1 kHz, 2 kHz, and 4 kHz. According to the results of the chi-square test statistical analysis, vertigo and comorbidities were associated with a poor prognosis of ISSNHL. Conclusion: In summary, the treatment outcomes of ISSNHL patients with initial total hearing loss were poor. There was a significant age-related difference with respect to marked recovery 1-month post-treatment, and the 18–30 y group showed better recovery than the other age groups.